PENGARUH PENGETAHUAN PERPAJAKAN, KESADARAN WAJIB PAJAK DAN SANKSI PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK KENDARAAN BERMOTOR SAMSAT KOTA BATAM - Zendrato, Eka Yudianto; Husda, Anggun Permata (LPPM Universitas Putera Batam, 2024)
This research aims to examine the factors that influence motor vehicle taxpayer compliance, namely the variables of tax knowledge, taxpayer awareness and tax sanctions. Motor vehicle tax is a form of regional income and is used for the benefit of the region as well. The population in this study are motor vehicle taxpayers registered with the Batam City Samsat who live in the Batam City sub-district. The sample in this study took a sample with an error rate of 10% using the Slovin formula. This research uses a quantitative method by distributing a Google Form questionnaire to 100 respondents as a sample with a Likert scale in this research. Then the data obtained was processed using SPSS V26. This research uses multiple linear regression analysis techniques. The results of this research with the tax knowledge variable influence motor vehicle taxpayer compliance with a significance of 0.000 < 0.05. The taxpayer awareness variable influences motor vehicle taxpayer compliance with a significance value of 0.020 < 0.05, and the tax sanctions variable influences motor vehicle taxpayer compliance with a significance value of 0.001 < 0.05. Based on the results of hypothesis testing in this research, it can be concluded that the variables of tax knowledge, taxpayer awareness and tax sanctions have a simultaneous effect on taxpayer compliance with Samsat motor vehicle tax in Batam City. Keywords: Tax knowledge, taxpayer awareness, tax sanctions, taxpayer compliance, motor vehicle tax